Penyaluran Aspirasi Kaum Muslimin Di Negara Demokrasi Dalam Perspektif Islam - Muin, Hijrayanti Sari (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Democracy is the political system of choice for many countries in the world. The choice of political system in a country has been determined by the country's constitution. Based on history, democracy is not a system that originates from Islamic teachings, this is a problem for Muslims who realize that all life arrangements must originate from Islam, so this causes the phenomenon of Muslims who do not want to be involved and do not want to use the rights that have been regulated by laws in democratic political agendas or activities. This research wants to answer the law on the use of the rights to express the aspirations of Muslims in democratic countries. This research uses a qualitative research method with a normative juridical approach, namely finding conformity between the contents of applicable laws regarding the rights of citizens in democratic countries and Islamic law. The results of this research state that channeling aspirations in a democratic system, namely taking part in elections and demonstrations, is based on the opinion of ulama with the principle of avoiding greater harm, so the law is permissible and even mandatory.